Logjams : a Look at Logjams and Emergent Wood Effects on Insect Emergence in a Small Northern Minnesota Stream - Snobl, Zachary (My University, 2012)
Wood performs vital functions in streams, such as trapping organic matter and creating pools. Less is known about how logjams affect insect emergence. It was hypothesized that the presence of wood and physical factors would increase the diversity of the emergent insect community. This study sampled a 40-m section of a small stream in Northern Minnesota, centered on a spanning logjam.
Color poster with text, photographs, and graphs.
Keywords: Wood--Biodegradation--Environmental aspects; Insects--Effect of water quality on; Stream ecology--Minnesota--Superior National Forest--Cabin Creek; Posters